ChemInform Abstract: Bifunctional Squaramide‐Catalyzed One‐Pot Sequential Michael Addition/Dearomative Bromination: Convenient Access to Optically Active Brominated Pyrazol‐5(4H)‐ones with Adjacent Quaternary and Tertiary Stereocenters. Issue 1 (7th January 2014) - Wang, Huanxia; Wang, Youming; Song, Haibin; Zhou, Zhenghong; Tang, Chuchi
Abstract An organocatalytic asymmetric simple process affords a wide variety of the title compounds in high yields with good to excellent diastereoselectivity and uniformly high levels of enantioselectivity from readily available starting materials.